Prevalence and Association of Different Levels of Intellectual Disability with Prenatal, Perinatal, Neonatal and Postnatal Factors: Prevalence and association of levels of ID - Naz, Shagufta; Ibrahim, Nazia; Sharif, Saima; Bashir, Naila; Sajjad, Eesha; Asghar, Iqra; Irshad, Saba; Firasat, Sabika; Kaul, Haiba; Sarwar, Sadia (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Intellectual disability (ID), also called mental retardation, is defined by below-average intelligence or mental aptitude as well as a lack of life skills. It has a significant association with residency, family history, and chromosomal disorder. An analytical cross-sectional study was performed over a period from December 2019 to January 2021 in special educations centers and hospitals of Lahore, Faisalabad, Shahkot, Sialkot, Gujranwala and Sangala, Punjab, Pakistan. This study was aimed to access the prevalence and risk factors of Intellectual disability (ID). Questionnaires were designed and filled with the help of general doctors, pediatricians, and psychiatrists who diagnosed both intellectual and adaptive functioning of individuals Association between these parameters was analyzed by using SPSS software (Chi-square test) between ID and risk factors and the level of significance was considered as P<0.05. The frequency of mild, moderate, severe, and profound ID was 46.7 %, 32.1 %, 14.6 %, and 6.7 % respectively. More males (56.82 %) as compared to females 43.17 % were observed.